Codex Alimentarius Commision: Procedural manual: Joint FAO/WHO Food Standards Programme Codex Alimentarius Commission - FAO (FAO, 1995)
The Manual is particularly useful for national delegations attending Codex meetings and for international organizations attending as observers. It will also be useful for Member Governments which wish to participate in Codex work by correspondence.